(untitled) (Revista de História Regional, 2007)
In recent years historical archaeologists have become increasingly interested in exploring how to use material culture to study conflict and how the interpretation of their sites is affected by modern perception. Grounded in a dialectical epistemology, the experience of past peoples is considered part of an ongoing social confrontation between social actors. Archaeologists tend to consider cultures as neatly bounded homogeneous entities. The holistic, monolithic nature of cultures has been put into question by several empirical and theoretical studies. In northeastern Brazil, a large maroon kingdom, Palmares, developed in the seventeenth century and people have often interpreted it in two ways. Some prefer to stress the African character of the polity, while others emphasize the diversity within the community. Archaeological research at Palmares produced evidence of a heterogeneous society, an interpretive model that does not follow dominant epistemological schemes and prejudices.